2022
DOI: 10.3390/w14152364
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Spatial Equilibrium Analysis of High-Quality Development Level in Mainland China Considering Water Constraints

Abstract: Water resources are indispensable to human society. High-quality development (HQD) is a multi-faceted, demanding, and sustainable pattern. High-quality development level (HQDL) is an indicator of regional development. Its quantitative calculation is helpful to intuitively understand the current regional development situation, and helps departments make timely adjustments. Spatial equilibrium degree (SED) reflects the development balance among regions. Understanding spatial equilibrium can clarify regional deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The results show that there is a negative, statistically significant dependence of the level of concentration of creative industries on the proportion of mono-industry. We consider [44], which showed that in panel data, all variables exceeded by the modulation of its root-mean-square error are significant. While the as the proportion of mono-industry increases, the diversification of creative industries occurs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results show that there is a negative, statistically significant dependence of the level of concentration of creative industries on the proportion of mono-industry. We consider [44], which showed that in panel data, all variables exceeded by the modulation of its root-mean-square error are significant. While the as the proportion of mono-industry increases, the diversification of creative industries occurs.…”
Section: Resultsmentioning
confidence: 99%
“…It should be pointed out that currently, scientific research uses different indexes of defining the concentration, including Gini [44,45], entropy [46], localization and Theil [47]. But empirical testing reveals that all concentration indexes have strong correlation [48].…”
Section: Dependent Variablementioning
confidence: 99%
“…When the spatial balance coefficient is 0, the spatial equilibrium level of water resources is the lowest. Therefore, in order to visually express the degree of spatial equilibrium of water resources, and based on the results of existing research [40,41], seven spatial equilibrium levels are set up in order with the interval of 0.2, as shown in Table 5.…”
Section: Spatial Equilibrium Assessment Of Water Allocationmentioning
confidence: 99%